AYURVEDIC MANAGEMENT OF PARIKARTIKA WSR FISSURE IN ANO : A CASE STUDY - Dhayagonde, Suresh Malakari; Desai, Sayaji (International Journal of Research -GRANTHAALAYAH, 2022)
Nowday’s hurry and worries lifestyle give rises to Ano rectal diseases. Fissure_in_ano in one of the most common disease found in society. Constipation, burning sensation at anal region, bleeding with stool are common symptoms of fissure_in_ano. In Ayurved its can compare with parikartika. 20 years old male patient suffering from guda daha, sarakta mala_prawrutti, malavshmbha, aanaha from last 10 days. With modern medicine he got temporary relief in guda daha but there is no relief in rest symptoms. For Ayurvedic treatment he came to our hospital. With first day he got relief and at the end of 5rd days he feel total cure.